PENERAPAN TEKNOLOGI BUDIDAYA IKAN NILA SISTEM BIONA DI KELOMPOK MINA SARI DESA LANDUNGSARI KABUPATEN MALANG - Anis Zubaidah; Riza Rahman Hakim (Universitas Mataram, 2023)
The Bio Natural system of fish farming technology (BIONA) is a fish farming system aims to create a balanced and environmentally friendly living environment for farmed fish by minimizes the use of chemicals that are harmful to humans and the environment. This technology has not been widely mastered by the general public. Even though this technology can be used as an alternative in fish farming with high productivity. Therefore, it is necessary to disseminate BIONA technology to the public. The method used in this activity is training and technology application, as well as partner assistance. The stages of the activity include BIONA technology training for tilapia cultivation, making BIONA technology demonstration plots, water media preparation, seed stocking, maintenance, feeding management, water quality management, and harvesting.. Furthermore, this group will become partners in the community service program. Based on the survey results, it was found that the problems in the partner group were: 1) lack of optimization of ponds for more productive fish farming, 2) lack of knowledge about tilapia cultivation technology. Referring to the problems experienced by the partner group, the solution offered is to provide training and assist partners on BIONA technology, which is an intensive fish farming system. So that the cultivation of tilapia will be more productive. The stages of activity include BIONA technology training for tilapia cultivation, making BIONA technology demonstration plots, water media preparation, seed stocking, maintenance, feeding management, water quality management, and harvesting. Tilapia harvesting is done after 5-6 months of maintenance, with an average size of 3-6 fish per kg and a survival rate of 92%. The appropriate technology for cultivating tilapia with the BIONA system has been well received by partners, because it can increase tilapia productivity, with high stocking densities and a survival rate of above 90%.